Impact of Alcohol Consumption on the Outcome of Catheter Ablation in Patients With Paroxysmal Atrial Fibrillation. Issue 12 (28th November 2016) - Takigawa, Masateru; Takahashi, Atsushi; Kuwahara, Taishi; Takahashi, Yoshihide; Okubo, Kenji; Nakashima, Emiko; Watari, Yuji; Nakajima, Jun; Yamao, Kazuya; Osaka, Yuki; Tanaka, Yasuaki; Kimura, Shigeki; et al.
Abstract : Background: Although several studies have reported an association between atrial fibrillation (AF) and alcohol, the impact of alcohol consumption on the outcome after catheter ablation (CA) for AF has not been discussed. We aimed to elucidate the effect of alcohol consumption on the outcome of CA for paroxysmal AF. Methods and Results: We examined 1361 consecutive patients with paroxysmal AF (mean age, 61±11 years, 334 women) who underwent CA, including 623 (45.8%) patients who consumed alcohol. The clinical characteristics and outcomes of CA were compared between patients who did and did not consume alcohol. No significant differences were seen in the left atrial size, duration of AF history, and incidence of nonpulmonary vein foci between 2 groups ( P =NS). Although the AF recurrence‐free rate after the initial CA was higher in patients who did not consume alcohol (261/623 [41.9%] versus 252/738 [34.1%]; mean follow‐up, 44.4±30.7 months; P =0.003), the outcome after the final CA was similar between 2 groups (patients who consumed alcohol: 111/628 [17.7%] versus patients who did not consume alcohol: 138/738 [18.7%]; mean follow‐up, 53.1±25.8 months; P =0.67). The frequency (hazard ratio 1.07 per 1 day/week increase, CI 1.00–1.15, P =0.04) of alcohol consumption was significantly associated with AF recurrence after CA. Conclusions: The frequency of alcohol consumption may be associated with AF recurrence after the initial CA for paroxysmal AF, but it may not affect the outcome after the final CA.